2011
DOI: 10.3141/2247-13
|View full text |Cite
|
Sign up to set email alerts
|

Much-Anticipated Marriage of Cycling and Transit

Abstract: In response to the environmental, economic, and social costs associated with overreliance on the automobile, planners and transportation professionals are promoting sustainable alternatives such as walking, cycling, and public transit, either as single modes or in combination. It has been argued that the marriage between cycling and transit presents opportunities for synergy by enlarging catchment areas of transit stations while drawing in new users to both of these green modes. However, because of the margina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 22 publications
2
56
0
Order By: Relevance
“…Perhaps due to the marginality of combining cycling and transit in North America, there is a shortage of reliable data and empirical studies on bicycle-transit integra tion (Bachand-Marleau et al 2011). For example, as of 2005, few transit agencies had collected detailed data about bicycle-on-transit rider characteristics or bicycle parking use (TRB 2005).…”
Section: Literaturementioning
confidence: 99%
“…Perhaps due to the marginality of combining cycling and transit in North America, there is a shortage of reliable data and empirical studies on bicycle-transit integra tion (Bachand-Marleau et al 2011). For example, as of 2005, few transit agencies had collected detailed data about bicycle-on-transit rider characteristics or bicycle parking use (TRB 2005).…”
Section: Literaturementioning
confidence: 99%
“…More commonly, studies focusing on cycling and walking assess the effect of facilities and services such as bicycle parking, workplace showers, and shared-use paths (Dill and Wardell 2007;Buehler 2012). In many studies, public transportation, walking, and cycling are considered complementary (Bachand-Marleau, Larsen, and El-Geneidy 2011;Pucher 2004). However, Boyd et al (2003) found a decrease in walking and cycling to campus after the fare-free public transportation program's introduction.…”
Section: Estimating the Impact Of Commuter Benefits On Mode Choicementioning
confidence: 99%
“…Many existing bicycle studies focus on identifying built environment factors that affect the bicycle use. These studies have discussed ways to encourage more bicycle use, such as building separated cycle tracks (Buehler & Pucher, 2012;Thomas & DeRobertis, 2013;Winters, Davidson, Kao, & Teschke, 2011), launching public bike sharing programs (Heinen, van Wee, & Maat, 2010;Shaheen, Guzman, & Zhang, 2010), promoting integration with public transit (Bachand-Marleau, Larsen, & El-Geneidy, 2011), and reducing vehicle parking in city centers (Shoup, 2005).…”
Section: 2mentioning
confidence: 99%